Rua do Prior, 41: Lotta Continua, the Carnation Revolution and the uses of the past in documentary cinema - Carvalho, Lorenzo d'Amico de (2022)
Based on the film Rua do Prior 41, by Lorenzo d’Amico de Carvalho, the two authors discuss the possibilities of representing the Carnation Revolution of April 1974 and the uses of memory. Crossing their gazes on historiographical interests, the use of image, creation and dissemination through theatre and cinema, Strippoli and d’Amico de Carvalho talk about the relationship between archival sources, literature, and mise en scène, for addressing the history of the largest Italian extra-parliamentary left-wing group of the seventies, Lotta Continua, and its connection to the April Revolution and the “Sixty-eight”. The text introduces the film and offers an interpretation about the relationship between the history of the revolution, the memory of the protagonists and the visuality of the past.